1994
DOI: 10.1172/jci117248
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radicals inhibit human plasma acetylhydrolase, the enzyme that catabolizes platelet-activating factor.

Abstract: Platelet-activating factor (PAF) can exert profound inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
8

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(68 citation statements)
references
References 73 publications
(70 reference statements)
2
58
0
8
Order By: Relevance
“…One possibility is that UVB could have inhibitory effects on PAF-acetylhydrolase enzymes. Indeed, oxidative stress has been reported to inactivate these enzymes that serve to degrade PAF and short-chained sn-2 glycerophosphocholines (44). A second possibility is that UVB is activating the PAF-R directly.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that UVB could have inhibitory effects on PAF-acetylhydrolase enzymes. Indeed, oxidative stress has been reported to inactivate these enzymes that serve to degrade PAF and short-chained sn-2 glycerophosphocholines (44). A second possibility is that UVB is activating the PAF-R directly.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in biological activity of oxidatively modified DFP * LDL we observe may be attributable to an increase in the amount of biologically active phospholipids, due to the loss of the initial hydrolytic activity provided by LDL-associated PAF-AH. It has previously been shown that oxidation depletes LDL of PAF hydrolytic activity (24,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…This has two implications. First, active oxygen species and oxidants are inhibitors of PAF acetylhydrolase (54). Second, the generation of these active oxygen species can lead to the formation of proinflammatory, oxidatively fragmented phospholipids, which also are degraded by PAF acetylhydrolase (55,56).…”
Section: Figurementioning
confidence: 99%